The Svalbard Church in Longyearbyen, Spitsbergen, As an Example of a Social Space in an Area with an Extremely Cold Climate - Magdalena Jagiełło-Kowalczyk, hab. inż. arch.; Agnieszka Żabicka, mgr inż. arch. (International Journal of Psychosocial Rehabilitation, 2024)
The main object of this study is the social space of the Svalbard Church (Svalbard Kirke in Longyearbyen on the island of Spitsbergen, a part of the Svalbard archipelago). It is an example of a social space that is atypical when European conditions are concerned. During the study of the architecture and urban layouts of Spitsbergen, as well as studying its inhabitants, the authors focused on the role and significance of social spaces in the lives of residents, their general characteristics and their positives and negatives, the manner of their use by various social groups, as well as their quality and functional solutions. The Svalbard Church, which is an example of a social space, was investigated while focusing on its characteristics as a place and on its context, the function and form of its architectural and urban layout, its structural system, construction materials, color, and its detail in reference to its distinct climate conditions. The goal of the study was to identify the quality of this space and its suitability to its users. The study was performed using critical analysis, on-site observation, and included a survey. The survey was performed among a group of respondents composed of the users of the investigated space, divided into the following age groups: 19 or younger, 20–25 years of age, 26–44 years of age, 45–66 years of age, and over 67 years of age.